Discussing the Extended Euclidean Algorithm

WARNING

This article was translated from Chinese by ChatGPT and may contain some errors.

Extended Euclidean Algorithm

The Euclidean Algorithm is an algorithm in number theory used to find the greatest common divisor c=(a,b)c=(a,b) of two integers aa and bb. I have previously explained that the correctness of this algorithm comes from (a,b)=(akb),kZ(a,b)=(a-k b), k\in \Z. The Extended Euclidean Algorithm is an algorithm that can obtain the coefficients ss and tt in

sa+tb=(a,b) sa+t b=(a,b)

The first time I saw the implementation of this algorithm was from a classmate who was proficient in algorithm competitions. His implementation was similar to

1int exgcd(int a,int b,int &x,int &y)
2{
3    if(b==0)
4    {
5        x = 1; y = 0; return a;
6    }
7    int r = exgcd(b, a % b, x, y);
8    int t = y;
9    y = x - (a / b) * y;
10    x = t;
11    return r;
12}

This implementation uses the parameters x and y as registers to pass the result, which has a strong imperative style.

A more understandable functional style implementation is as follows:

1let rec ext_gcd a b = 
2  if b = 0 then (1, 0, a)
3  else 
4    let quo = a / b
5    let r = a % b
6    let (s, t, gcd) = ext_gcd b r
7    (t, s - quo * t, gcd)

In fact, both of the above implementations are based on a manual substitution process. Take the following Euclidean algorithm process as an example:

20÷7=2...67÷6=1...16÷1=6...0 20 \div 7 = 2 ... 6 \\ 7 \div 6 = 1 ... 1 \\ 6 \div 1 = 6 ... 0

Change each division formula into an addition and subtraction formula of the previous division:

202×7=671×6=161×6=0 \begin{aligned} 20 - 2 \times 7 = 6 \\ 7 - 1 \times 6 = 1 \\ 6 - 1 \times 6 = 0 \end{aligned}

Consider the penultimate formula

71×6=1 7 - 1 \times \textcolor{red}{6} = 1

Replace the 6\textcolor{red}{6} in this formula with 202×7=620 - 2 \times 7 = \textcolor{red}{6}, we get:

71×(202×7)=11×20+3×7=1 7 - 1 \times (20 - 2 \times 7) = 1 \\ -1 \times 20 + 3 \times 7 = 1

More generally, the two formulas are

s1a1+t1b1=c1s2b1+t2c1=c2 \begin{aligned} s_1 a_1 + t_1 b_1 = c_1 \\ s_2 b_1 + t_2 c_1 = c_2 \end{aligned}

Then, if we merge and substitute them, it will become:

(s1t2)a1+(s2+t1t2)b1=c2 (s_1 t_2) a_1 + (s_2 + t_1 t_2) b_1 = c_2

Obviously, this process can be abstracted into an operation on a triplet, represented here by *, that is:

(s1,t1,c1)(s2,t2,c2)=(s1t2,s2+t1t2,c2) (s_1, t_1, c_1) * (s_2,t_2,c_2)=(s_1t_2, s_2 + t_1 t_2, c_2)

Looking at the functional program again, we will be much clearer:

ext_gcd b r gets the triplet (s,t,gcd)(s, t, gcd) of sb+tr=gcds b + tr = gcd, and this triplet can perform the * operation with the triplet (1,quo,r)(1, -quo, r) of 1×a+(quo)×b=r1 \times a + (-quo) \times b = r defined by this division, and

(1,quo,r)(s,t,gcd)=(t,s(quo)t,gcd) (1, -quo, r) * (s, t, gcd) = (t, s-(quo)t, gcd)

This is exactly the return value (t, s - quo * t, gcd) in the code.

We can give a program that directly uses this operation:

1let F x1 x2 = 
2  let s1, t1, c1 = x1
3  let s2, t2, c2 = x2 
4  (s1 * t2, s2 + t1 * t2, c2)
5
6let rec ext_gcd2 a b =
7  if b = 0 then (1, 0, a)
8  else 
9    let quo = a / b
10    let r = a % b
11    F (1, -quo, r) (ext_gcd2 b r)

From recursion to loop

Wands pattern

More than 40 years ago, MITCHELL WAND published a paper called Continuation-Based Program Transformation Strategies, in which he summarized many general methods for transforming recursive programs into loop programs.

Of course, the real meaning of loop and recursion here needs further specification, for example,

1(define (factor n)
2  (let loop ([n n] [cont (lambda (x) x)])
3    (if (= n 0)
4        (cont 1)
5        (loop (- n 1) (lambda (x) (cont (* n x)))))))

This kind of loop is not the loop studied here, the loop we are talking about must be something with fixed space, space complexity of O(1)O(1).

By studying two ways of writing functions similar to factor:

1(define (factor n)
2  (if (= n 0)
3      1
4      (* n (factor (- n 1)))))
1(define (factor n)
2  (let loop ([n n][acc 1])
3    (if (= n 0)
4        acc
5        (loop (- n 1) (* acc now)))))

WAND summarized the first pattern:

The requirement is that bb is an operation of AAAA \rightarrow A \rightarrow A and has associativity, where lbl_b is the right unit element (meaning b(x,lb)=xb(x, l_b)=x).

Can we use this pattern to transform the above program? It seems possible, because here p(x)p(x), a(x)a(x), bb, FF, c(x)c(x), d(x)d(x) can be clearly given.

However, there is a problem: is the operation * defined above associative?

Associativity?

The associativity of an operation essentially describes whether this operation can change its operation order when it is self-combined. Consider an operation ff, it has associativity, that is to say

f(a,f(b,c))=f(f(a,b),c) f(a,f(b, c))=f(f(a, b), c)

However, our operation seems to be non-associative:

Whats going on? Lets study a specific example:

(54,12)=11×55+(3)×16=7,(1,3,7)1×16+(2)×7=2,(1,2,2)1×7+(3)×2=1,(1,3,1)1×2+(2)×1=0,(1,2,0) (54, 12) = 1 \\ 1 \times 55 + (-3) \times 16 = 7, (1, -3, 7) \\ 1 \times 16 + (-2) \times 7 = 2, (1, -2, 2) \\ 1 \times 7 + (-3) \times 2 = 1, (1, -3, 1) \\ 1 \times 2 + (-2) \times 1 = 0, (1, -2, 0) \\

Take the first three as examples, if you do it in the correct order:

This will result in a very surprising result, because

6×5520×16=10 6 \times 55 - 20 \times 16 = 10

And our combined operation should theoretically yield

6×5520×16=1 6 \times 55 - 20 \times 16 = 1

Where is the problem?

Consider (1,3,7)(1,2,2)=(2,7,2)(1, -3, 7) * (1, -2, 2)=(-2, 7, 2), the meaning of the triplet on the right side of the equation is:

2×55+7×16=2 -2 \times 55 + 7 \times 16 = 2

This equation cannot be operated with

1×7+(3)×2=1 1 \times 7 + (-3) \times 2 = 1

using \*\*. Because the equation that can be operated with 2×55+7×16=2-2 \times 55 + 7 \times 16 = 2 using * must be in the form of

a×16+b×2=c a \times 16 + b \times 2 = c

As you can see, this is not just a problem of lack of associativity. For the \*\* operation we defined, (a\*b)\*c(a\*b)\*c has no meaning at all.

In this way, it is impossible to transform this recursion into a loop simply by using Wangs method.

How to implement in a loop?

Observe the equation above again

1×55+(3)×16=7,(1,3,7)1×16+(2)×7=2,(1,2,2)1×7+(3)×2=1,(1,3,1) 1 \times 55 + (-3) \times 16 = \textcolor{red}{7}, (1, -3, 7) \\ 1 \times 16 + (-2) \times \textcolor{red}{7} = \textcolor{blue}{2}, (1, -2, 2) \\ 1 \times \textcolor{red}{7} + (-3) \times \textcolor{blue}{2} = 1, (1, -3, 1) \\

We seem to have discovered a new pattern:

sn2a1+tn2b1=cn2sn1a1+tn1b1=cn1scn2+tcn1=c3 s_{n-2} a_1 + t_{n-2} b_1 = c_{n-2} \\ s_{n-1} a_1 + t_{n-1} b_1 = c_{n-1} \\ s c_{n-2} + t c_{n-1} = c_3

If the above relationship can be established, then sns_n and tnt_n can be calculated:

s(sn2a1+tn2b1)+t(sn1a1+tn1b1)=c3sn=ssn2+tsn1tn=stn2+ttn1 s (s_{n-2} a_1 + t_{n-2} b_1) + t (s_{n-1} a_1 + t_{n-1} b_1) = c_3 \\ s_n = ss_{n-2}+ ts_{n-1} \\ t_n = st_{n-2}+tt_{n-1}

The headache is the establishment of the first two equations. In fact, if the reader has carefully studied the recursive version of the algorithm, the establishment of the last equation uses an interesting technique. We can also use the same technique here, but why this technique works is left to the reader to study:

s0=1,t0=0s1=0,t1=1 s_0 = 1, t_0 = 0 \\ s_1 = 0, t_1 = 1

The implementation is as follows:

1let rec ext_gcd_loop a b =
2  if b = 0 then (1, 0, a)
3  else 
4    let rec loop a b s_n1 t_n1 s_n2 t_n2 = 
5      let quo = a / b 
6      let r = a % b
7      let s = 1
8      let t = -quo
9      if r = 0 then (s_n1, t_n1, b)
10      else 
11        loop b r (s * s_n2 + t * s_n1) (s * t_n2 + t * t_n1) s_n1 t_n1
12    loop a b 0 1 1 0